Bidirectional relationship between health and economy in Colombia. Regional case (2019)
The purpose of this final report of the investigation “bidirectional relationship betweenhealth and economics at Colombia. Regional event “was to analyze the health andeconomic growth relationship for Colombian regions with two approaches: 1) microand 2) macroeconomic 1) Information National Survey of Quality of Life (DANE-CVD / 2008) in nine regions,cross-section [methodology Becker and Chiswick (1966); Mincer (1974)], extendedwith health. Bidirectional health and hourly wage was not proven; correlation was nofound between them. The transition from a state of ill-health regulate other goodvery good hourly wage increased 15% on average. 2) Information National Accounts(DANE), -Panel 25 departments and five year periods, 1990-2010; extended Solowmodel (MRW, 1992) expanded health, aggregate production function Cobb-Douglas(Barro, 1996a) production. Significant correlation between spending-health, GDP,total assets, expense-education and PEA, coefficients above 0,86 was found; Low-costhealth, crude death rate, life expectancy and infant mortality, with values lower than0,45 correlation. When economic growth increases departments, increased level oflife expectancy; however, after a certain level, the behavior of the curve flattens lifeexpectancy (Preston, 1975).